Measuring spirituality and religiosity in clinical research: a systematic review of instruments available in the Portuguese language - Lucchetti, Giancarlo (2013)
CONTEXT AND OBJECTIVES: Despite numerous spirituality and/or religiosity (S/R) measurement tools for use in research worldwide, there is little information on S/R instruments in the Portuguese language. The aim of the present study was to map out the S/R scales available for research in the Portuguese language. DESIGN AND SETTING: Systematic review of studies found in databases. METHODS: A systematic review was conducted in three phases. Phases 1 and 2: articles in Portuguese, Spanish and English, published up to November 2011, dealing with the Portuguese translation and/or validation of S/R measurement tools for clinical research, were selected from six databases. Phase 3: the instruments were grouped according to authorship, cross-cultural adaptation, internal consistency, concurrent and discriminative validity and test-retest procedures. RESULTS: Twenty instruments were found. Forty-five percent of these evaluated religiosity, 40% spirituality, 10% religious/spiritual coping and 5% S/R. Among these, 90% had been produced in (n = 3) or translated to (n = 15) Brazilian Portuguese and two (10%) solely to European Portuguese. Nevertheless, the majority of the instruments had not undergone in-depth psychometric analysis. Only 40% of the instruments presented concurrent validity, 45% discriminative validity and 15% a test-retest procedure. The characteristics of each instrument were analyzed separately, yielding advantages, disadvantages and psychometric properties. CONCLUSION: Currently, 20 instruments for measuring S/R are available in the Portuguese language. Most have been translated (n = 15) or developed (n = 3) in Brazil and present good internal consistency. Nevertheless, few instruments have been assessed regarding all their psychometric qualities.